Impact of comorbid Chronic Rhinosinusitis with Nasal Polyp (CRS wNP) on Asthma Severity in a Specialized Clinical Setting (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) and asthma are common comorbid conditions affecting upper and lower airways.  Their coexistence is associated with increased morbidity rates and a synergistic risk of exacerbation, leading to a substantial clinical burden. A unified airway approach is often recommended, emphasize coordinated management rather treating each condition separately.  This study aimed to evaluate the clinical, biochemical and radiological correlations, between CRSwNP severity and the level of asthma control, as well as treatment outcomes.Methods: This retrospective observational study was conducted in the department of otolaryngology at Bangladesh Medical University (BMU) over a period of three years. A total 130 participants were included. All participants underwent detailed clinical evaluation and laboratory investigation including Complete blood count (CBC), eosinophil count and serum IgE level. Radiological severity was assessed using computed tomography (CT) of the paranasal sinuses applying Lund- Mackay Scoring System.  Patients received either medical therapy alone or a combination of medical and surgical intervention. Outcomes were evaluated after 6- month follow- up period.Results: The study population (n=130) ranged in age from 25 years to 70 years with a median age of 47.5 years. The male to female ratio was 1.8:1. The most common symptoms were nasal obstruction (84%). Rhinorrhea (78%) and hyposmia (68%). Biochemical markers were significantly elevated (p